(3hajGJ GdeYUhejfs - (3eLghds
(3ChdgG (B:s
(3aj HjGf JGQjN hdGOI SjO GdeQSdjf hNGJe GdfHjjf hMHjH QH GdYGdejfs
(3BNQgG (B:s
(3hbO PcQhG aj YdGeGJ XghQg CehQG cKjQI(B... (3hgPG TjA PcQfGg(B... (3dG JjefG hJHQcG Hg hCf jchf GdNJGe eScG (B...s
(3JHUQI GdeDda (B:s
(3jfSH gPG GdcJGH aj GdCYdGe(B: (3L(B:6(3,U(B302 (3deMeO Ydj Hf ejQRG eMeO GdTGg YHO GdYXjej GdfLaj, J(B: 1334(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3,U(B302s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJGQjNs